Leishmania donovani Activates Hypoxia Inducible Factor-1α and miR-210 for Survival in Macrophages by Downregulation of NF-κB Mediated Pro-inflammatory Immune Response - Kumar, Vinod; Kumar, Ajay; Das, Sushmita; Kumar, Ashish; Abhishek, Kumar; Verma, Sudha; Mandal, Abhishek; Singh, Rakesh K.; Das, Pradeep (Frontiers in Microbiology, 2018)
Abstract Micro RNAs (miRNAs) have emerged as a critical regulator of several biological processes in both, animals and plants. They are also associated with regulation of immune responses in many human diseases during recent years. Visceral leishmaniasis (VL) is the most severe form of leishmaniasis, which is characterized by impairment of both, innate and adaptive immune responses. In the present study, we observed that Leishmania establishes hypoxic environment in host macrophages that induces the expression of hypoxia inducible factor-1α (HIF-1α) and miRNA-210. Further, the expression of miRNA-210 was found to be dependent on activation of HIF-1α expression. The HIF-1α silencing by siRNA resulted in significantly (p<0.001) decreased expression of miR-210 in parasites infected macrophages. We also observed that in siHIF-1α or antagomir-210 treated L. donovani infected macrophages, the parasitic load and percentage infectivity was significantly (p<0.001) decreased. Furthermore, we found that inhibition of miR-210 resulted in activation of NF-κB subunit p50 and forms heterodimer with p65 and its translocates into nucleus from cytoplasm. This significantly (p<0.05) induced the transcription of pro-inflammatory cytokines genes such as TNF-α and IL-12 in miRNA-210 inhibited macrophages as compared to uninhibited macrophages whereas the level of IL-10, an anti-inflammatory cytokine, was found decreased (p<0.001). These findings suggested that L. donovani infection induces hypoxic environment inside the macrophages that activates HIF-1α. Further, HIF-1α up regulates miR-210, which eventually establishes a suitable environment for survival of parasite inside the host macrophages by down regulating NF-κB mediated pro-inflammatory immune responses.